New Lightning‐Derived Vertical Total Electron Content Data Provide Unique Global Ionospheric Measurements. Issue 5 (18th May 2022) - Lay, Erin H.; Tippmann, Jeffery D.; Wiens, Kyle C.; McDonald, Sarah E.; Mannucci, Anthony J.; Pi, Xiaoqing; Coster, Anthea; Kippen, R. Marc; Peterson, Michael J.; Redmon, Rob
Abstract: A newly released, novel ionospheric data set of global gridded vertical total electron content (VTEC) is introduced in this paper. This VTEC data set, provided by Los Alamos National Laboratory (LANL), is derived from very high frequency (VHF; defined as 30–300 MHz) broadband radio‐frequency (RF) measurements of lightning made by U.S. Department of Defense sensing systems on board Global Positioning System (GPS) satellites. This paper presents the new data set (LANL VTEC), discusses the errors inherent in VHF TEC estimation due to ionospheric dispersion, and compares the LANL VTEC to two community standard VTEC gridded products: Jet Propulsion Laboratory's Global Ionospheric Model (JPL GIM) and the CEDAR community's Open Madrigal VTEC gridded measurements of L‐band GNSS (global navigation satellite systems) TEC. We find that the LANL VTEC data have an offset of 3 TECU from CEDAR Madrigal GNSS VTEC and a full‐width‐half‐maximum (FWHM) of 6 TECU. In comparison, the offset between LANL VTEC and the JPL GIM model is −3 TECU, but with a FWHM of 5 TECU. We also compare to Jason‐3 VTEC measurements over the ocean, finding an offset of less than 0.5 TECU and an FWHM of <5 TECU. Because this technique uses a completely different methodology to determine TEC, the sources of errors are distinct from the typical ground‐based GNSS L‐band (GHz) TEC measurements. Also, because it is derived from RF lightning signals, this data set provides measurements in regions that are not well covered by ground‐based GPS measurements, such as over oceans and over central Africa. Plain Language Summary: The ionosphere is a region of the atmosphere that is very important in communications between ground and satellite. For that reason, decades of scientific effort have been put toward developing models of the ionosphere so that we can more accurately predict what the state of the ionosphere is at any given location and time. A general product produced by many of these models is the vertical total electron content (VTEC), which is the vertically integrated electron density at a particular location at a particular time. The majority of these models use measurements of TEC from ground‐based receivers or instruments, meaning that abundant measurements that go into the models often lack data from over the oceans or in technologically limited regions of the world (e.g., Africa). Here, we present a new VTEC data set that is derived from lightning strokes detected with U.S. Department of Defense sensing systems on GPS satellites. Because the data set uses naturally occurring lightning for its source, it does not have the same limitations as ground‐based TEC measurements and can provide an additional source of validation data for ionospheric models. We introduce the data set and compare it with community‐accepted VTEC models and measurements. Key Points: New global gridded vertical total electron content (VTEC) data set derived from radio‐frequency measurements from lightning emissions during the entire year of 2018 has been released VTEC product adds new global coverage in areas with few global navigation satellite systems receivers (ocean and continental Africa) The VTEC values, generated from very high frequency radio‐frequency data, show bias in Madrigral data set and differences to Jet propulsion laboratory's global ionospheric model model‐derived VTEC